How do you simplify 3x ( 2x + 3) - 4( x ^ { 2} - 2x) 3x(2x+3)−4(x2−2x)?
2 Answers
Explanation:
1) First, multiply the bracket(s) out, this gets us:
=>
=>
=>
=>
Since
2) Plug this back into the expression, replacing the brackets before with the answers we just got gets us:
3) Collect like-terms to simplify this further:
4) Then plug this back into the expression, as it is fully simplified. Leaving us with:
Explanation:
"distribute brackets and collect like terms"
=color(red)(6x^2)color(blue)(+9x)color(red)(-4x^2)color(blue)(+8x)
=2x^2+17x